PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TEKNIK KANCING GEMERINCING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN SUBANG ANAK KABUPATEN TANAH DATAR. - Wati, Yulia; Angraini, Villia; Pratiwi, Merina (STKIP PGRI Sumbar, 2013)
The comprehension in mathematics concept for students is still low becomes a basic of this research. The purpose of this research is to know what is the comprehension of mathematic concept for cooperatif learning type Pair Kancing Gemerincing better than for implementation of convensional learningâs students for grade VIII MTsN Subang Anak Kabupaten Tanah Datar. The type of this research is experimental research by using random planning focused on subject. The populations are students in grade VIII MTsN Subang Anak Kabupaten Tanah datar, which consist of five classes. Moreover, sample of this research is taken by random, VIII3 is for experimental class and VIII2 is for control class. The instrument of this research is the comprehension of mathematics concept test. The techniques of data analysis is using t test for one group by software MINITAB is got P-value < , so this hyphothesis is accepted. In conclusion, the comprehension of mathematics concept for implemented convensional learningâs students. So, inferential The purpose of this research is to know what is the comprehension of mathematic concept for cooperatif learning type Pair Kancing Gemerincing better than for implementation of convensional learningâs students for grade VIII MTsN Subang Anak Kabupaten Tanah Data